Recognizing Arabic alphabet by segmentation in Quran document / Mohd Firdaus Amran - Amran, Mohd Firdaus (2009)
Recognition by segmentation of Arabic characters on scanned images has enabled many applications such as recognition for characters in certain volume of documents, automatic sorting of postal mail (in certain countries) and convenient editing of previously printed documents. This paper provides a comprehensive review of method in segmenting focusing on source of one main document that is Al-Quran. Quran in Islamic definition is the sacred writings of Islam revealed by God to the prophet Muhammad during his life at Mecca and Medina [1]. It has been written in Arabic as it was developed in that region. As Islam in become one of the biggest religious in the globe is known have many race in different country that believe as their manual of life. Research will provide segmentation rates and description of algorithm for the approaches discussed. It describes background on the field, discussion of the methods, and future research directions.